KEY PROPOSALS FOR THE NEXT GOVERNMENT: NEITHER MERCANTILIST, NOR POPULIST - Romero Cerna, José Salvador (2015)
The presidential elections will be held next April, and although it expected that a second round will occur, election proposals that defend the current growth model followed by the last three governments (on the basis of the reforms imposed after the coup and dissolution of Congress of April 5, 1992), there is still the possibility that an electoral alternative may arise breaking the status quo in the second round. Therefore is necessary that the presidential candidates (right and left) define their government proposals regarding the following issues: 1) the management of interest conflicts and lobbies, 2) the designation of the principal public officials (operators) and public institutions of the executive power, 3) the business activity of the Government and 4) The reform of the Private Pension System (SPP). If electoral proposals that represent the status quo pass to the second round, we need that the candidates define their proposals on the first two issues, since the business activity of the Government and reform of the SPP would not be modified. An electoral alternative proposal would change the status quo of these issues. The transparency of the electoral proposals targets the lowering of profiteering and populism cases at the end of the next government (either right or left).